Forma escolar dos aldeamentos jesuíticos do século XVI - Melo, Jéssica Cristine de (2023)
The present research consists of the study of the Jesuit settlements of the 16th century, spaces dedicated to the conversion and education of the Indians. Therefore, the aim is to understand the school form used in these places, where individuals were confined and disciplined to form docile bodies, a concept developed by the author Michel Foucault, in his book Discipline and Punish: The Birth of the Prison. For the understanding of the concept of school form, this investigation resort authors such as Guy Vincent, Bernard Lahire and Daniel Thin, who discuss this concept from a historical approach. This research is based on the qualitative paradigm, because presents a theoretical design substantiated on analysis of Jesuit letters and documents prepared by the Society of Jesus, along with studies by researchers who write about Jesuit education, including historians, anthropologists, education specialists. It can be understood that the school form corresponds to a mode of socialization, which is configured according to some assumptions, such as a specific space, its own pedagogy, in addition to organization through rules and schedules. Thus, the results indicate that the Jesuits, in the referred settlements, considering their customs (rules, schedules, disciplinary pedagogies) and traditions of the catholic faith and European principles, acted in the mission of converting and educating the indigenous people, so that could turn them into catholics and subjects of the king.